STRUCTURAL SEMIOTICS IN THE PLAY "AMIRAH AL ANDALUS" BY TEATER OASE (A SEMIOTIC ANALYSIS BASED ON CHARLES SANDERS PEIRCE'S THEORY) - Wiwin Kasih Rahayu; Nurul Musyafa’ah; Muhammad Afthon Ulin Nuha (Jurnal Bindo Sastra, 2025)
Semiotic theory is useful for several reasons that are easy to understand. Semiotic theory is very flexible and can be applied to different types of media and texts, such as film, literature, advertising, and art, making research in various fields possible. Through the semiotic approach, we can see how symbols and signs are influenced and affect the social and cultural context. This study aims to describe the intrinsic elements of the drama Amirah Al-Andalus, using Charles Sander Peirce's semiotic signs. The meaning of the play is obtained through signs and their references (icons, indexes, and symbols).  The data source of this research is the Amirah al-Andalus theater text directed by Oase theater. Amirah Al-Andalus theater script written by Arabic Literature students of Surakarta State University was published in 2022. This research is a qualitative descriptive research. Descriptive data is obtained through reading and note-taking techniques.  The results of the study are as follows.  1) Intrinsic elements include plot, setting, characterization, and theme. 2) Charles Sander Pierce's semiotics in this study is in the form of interpretation, representamen and object, then the relationship between the representamen and the object continues, namely icons, indexes and symbols. 3) The results of semiotic structural analysis in this study are in the form of icons, indices and symbols.